Extraction of essential oil from Murraya Koenigii leaves using ultrasonic-assisted solvent extraction method - Za Iskandar, Mohd Dikui (2009)
The objective of this research is to extract essential oils from M. koenigii leaves by using ultrasonic-assisted solvent extraction method. The major constituent of M. koenigii has been reported as caryophyllene and 3-carene which is responsible for the aroma and flavor. This research has focused on the influence of ultrasonic, various natures of solvents, sonication times and also drying method towards the extraction of M.koenigii essential oil. Two types of solvents are used in this research which is ethanol and hexane. In this research, the methods of drying, grinding, extraction, separation and analysis are used and the sample is separated from solvents by using a rotary evaporator to get the essential oil. The sample was analyzed by using a GC-MS to identify the component of M. koenigii essential oil. In this research, the most suitable solvent to produce higher percentage yield is by using ethanol (ultrasonic-assisted solvent extraction of fresh leaves for 30 minutes) and the percentage of oil yield also increased with increasing the time. The major component in M. koenigii leaves is caryophyllene and hexane on the other hand is the best solvent to be used to extract caryophyllene.